Exploring Income Convergence for Central and South Asia - Gul, Hameed; ul Haq, Ihtisham; Khan, Dilawar; Allayarov, Piratdin; Abbas, Khurram (Comparative Economic Research. Central and Eastern Europe, 2024)
Income convergence refers to the idea that poor countries grow more quickly than rich ones and catch up in terms of per capita income; as a result, the per capita income of integrated nations eventually converges. Beta convergence suggests that less developed nations grow more quickly than more developed ones and reach their average per capita income level by growing more quickly. Meanwhile, sigma convergence suggests that the per capita income disparity among the countries in a regional block narrows over time. The objective of this study is to test income convergence through beta and sigma convergence for Central and South Asia integration using data from 1990 to 2022. Sigma convergence is tested through the standard deviation and coefficient of variation of average per capita income, while beta convergence is tested using panel unit root tests. The results of the study confirm the beta convergence and sigma convergence, which implies income convergence for the integration of Central and South Asia. The implications of this study are manifold. It recommends that Central and South Asian countries ensure economic, political and social cooperation with one another. This is possible by eliminating trade restrictions and decreasing import taxes to increase free trade. Additionally, ensuring free labor, capital, and technology movement between Central and South Asia will be beneficial for ensuring economic integration, facilitating income convergence, and reducing income inequality between these regions. This study contributes to the income convergence literature by focusing on integration between Central Asia and South Asia.